HISTORICAL ASPECTS, EVENTS AND PERSPECTIVES OF DEVELOPMENT IN THE VIDEOLAPAROSCOPIC SURGERY - Bychkov, S.A.; Grynyov, R.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The article is devoted to history, modern state and prospects of development of one of the most dynamically developing directions of modern medicine - videolaparoscopic surgery. Historical landmarks, famous scientists doing considerable contribution to development of this field of surgery, are described. Modern technologies introduction of which in the near future is able cardinally to change the face of medicine are also described.